A Note on Indifference Pricing with Dynamic Quasiconcave Preferences. (17th July 2015) - Giammarino, Flavia
<x xml:space="preserve">Abstract</x> In this paper we study the problem of indifference pricing in a discrete‐time setting where the decision‐maker's preferences are represented by a general monotone increasing and quasiconcave dynamic preference functional. We show that the indifference price is a dynamic convex risk measure and we introduce as an example the dynamic robust entropic risk measure.